Ubiquitous access to cultural tourism portals - Garzotto, F.; Paolini, P.; Speroni, M.; Proll, B.; Retschitzegger, W.; Schwinger, W. (Proceedings. 15th International Workshop on Database and Expert Systems Applications, 2004, 2004)
Web-based tourism information systems are more and more required to provide besides traditional tourism information about hotel facilities and infrastructure also cultural content comprising material heritage, performing art, folk tradition, handicraft or simply habits of everyday life. These cultural Web applications are required not to offer online brochures only, but rather to provide both, value and service. This paper focuses on two crucial aspects of cultural Web applications comprising quality of content and quality of access. As an example for achieving quality of content in terms of comprehensiveness and cross-national nature, the MEDINA portal is presented, allowing one-stop access to cultural information of fourteen Mediterranean countries. In order to provide quality of access, the notion of ubiquity is introduced, allowing to customize Web applications towards different kinds of contexts, thus supporting the cultural tourist with device-independent, time-aware, location-aware, and personalized services.